Communicative Characteristics of Education of Primary Class Students on the Basis of An Innovative Approach - Khudoymurodova Dilafruz Jonpolatovna (Zien Journals, 2022)
The article describes the types of use of today's innovative interactive methods and its advantages for elementary school teachers based on an innovative approach. The necessity of such a technological approach, its importance and the development of professional training, the achievement of the principles of consistency, systematicity and the use of innovative technologies in education. As a result of the study, pedagogical methods, forms of educational organization, and issues of clarifying the role of learners in the organization of the educational process were interpreted.
Keywords: innovation; interactive; information technologies; independent thinking